Children With Dyslexia and Familial Risk for Dyslexia Present Atypical Development of the Neuronal Phonological Network - Łuniewska, Magdalena; Chyl, Katarzyna; Dębska, Agnieszka; Banaszkiewicz, Anna; Żelechowska, Agata; Marchewka, Artur; Grabowska, Anna; Jednoróg, Katarzyna (Frontiers in Neuroscience, 2019)
Learning to read changes the brain language system. Phonological processing is the language domain most crucial for reading, but it is still unknown how reading acquisition modifies the neural phonological network in children who either develop dyslexia or are at risk of dyslexia. For the two first years of formal education, we followed 90 beginning readers with (n = 55) and without (n = 35) familial risk of dyslexia who became typical readers (n = 70) or developed dyslexia (n = 20). We used functional magnetic resonance imaging to identify the neural correlates of phonological awareness using an auditory rhyme judgement task. This task was applied when participants were starting formal education, and repeated two years later. By applying two alternative group splits, we analysed the effects of dyslexia and the effects of familial risk of dyslexia separately. We found that the phonological brain network undergoes reorganization during the first two years of formal education. This process proceeds differently depending on the presence of a familial history of dyslexia and reading impairment. Typical readers without risk for dyslexia activate structures responsible for phonological processing already at the beginning of literacy. This group shows reduced brain activation over time during phonological processing, perhaps due to automatization of phonological skills. Children who develop reading impairment present a delay in the development of phonological structures such as the bilateral superior temporal gyrus, middle temporal gyrus, supramarginal gyrus and Heschl’s gyri, where we observed time and group interaction. Finally, typical readers with familial risk of dyslexia also present an atypical development of the neural phonological structures, visible both at the beginning of reading instruction and two years later. These children used a presumably efficient neural mechanism of phonological processing, based on the activation of the precentral and postcentral gyri, and achieved a typical level of phonological awareness.